Web profile development for furniture business in UD Rozi Rachmad, Surabaya City - Tracy Olivia; Devandro Alifiano; Fajrul Fallah Arrafi; Riza Akhsani Setyo Prayoga; Rizky Fenaldo Maulana; Nicko Nur Rakhmaddian (University of Merdeka Malang, 2023)
The development of information technology is accelerating. Many activities use information technology to do their jobs better. Currently, promotional media is not only through print media but can also use websites as a means of reaching consumers widely. The presence of a website has a positive impact, one of which is being able to get information from anywhere and anytime. This provides a good solution to one of Surabaya's micro, small, and medium enterprises engaged in furniture, namely UD Rozi Rachmad, whose business has been in Surabaya for a long time. The development of this website uses parallel development, and this website is assisted by the use of WordPress, additional themes, and additional plugins. Website testing has been carried out and is in accordance with the expected results with the black box testing method. So that the quality of the web is quite good when several black box tests have been carried out with procedures that have been carried out on testing, It is hoped that the presence of this website can help with promotional media and introduce their products to a wider audience of consumers. Consumers can also transact through the website, making it easier for consumers to shop when they are outside of Surabaya.